Manajemen Strategi Humas dalam Menciptakan School Branding melalui Ekstrakurikuler - Violetasari, Audrea Maharani; Rohmadi, Syamsul Huda (Universitas Pahlawan Tuanku Tambusai, 2024)
Branding focuses on the unique criteria of excellence presented in schools, thus creating an attraction and public trust to register at the school. However, the involvement of parents and alumni is still lacking in school activities. In fact, their participation can be an effective way to strengthen school branding through word-of-mouth or positive testimonials. This research was conducted using qualitative research, so the methods used in this study were interviews and observations. The researcher used a case study research approach. Data collection carried out by researchers was qualitative, by reducing data, presenting data and drawing conclusions and using observation, interview and documentation techniques. The selection of extracurricular activities that are tailored to the interests of students has an important role in school branding. Branding strategy through extracurricular activities, schools can improve their reputation and attract new students every year. This is realized by the increasing number of students every year.